CHEMICAL AND FREE FATTY ACID COMPOSITION OF GOAT MILK CHEESE RIPENED WITH Lactobacillus acidophilus AND EXTRACT RABBIT STOMACH AS COAGULANT - Indratiningsih, Nurliyani, Sulvia Dwi Astuti & (Proceeding of International Congress, 2014)
Rabbit stomach is waste from rabbit slaughtering that has the potential to be used as an alternativesource of rennet for cheese production. The purpose of this study was to determine the effect of ripeningby using Lactobacillus acidophilus on the chemical composition and free fatty acids (FFA) profile ofgoat milk cheese with extract of rabbit stomach as coagulant. Lactobacillus acidophilus (1%) was inoculatedinto pasteurized goat milk and incubated for 1 h, rennet extract up to 3% was added and incubatedfor 25 min. Cheese was stored at 4Î¿C for 42 d. The moisture, fat, protein and ash content wereanalyzed at day 0, 21 and 42, whereas the FFA of goat milk cheese were analyzed on day 0 and 42. Therewere significantly differences in the moisture, protein, and ash content in the goat milk cheese on 21 and42 days of ripening, but there was no significant difference in the fat content. The longâchain saturated(C16:0 and C18:0) and unsaturated (C18:2) FFA were the most abundant in goat milk cheese, and therewere no significant differences between pre or post ripening. The concentration of short chain fattyacid (C6:0, C8:0 and C10:0) and the overall concentration of FFA in goat milk cheese after 42 days ripeningwas higher compared to those preâripening.Keywords: Chemical composition, Free fatty acid, Goat milk cheese, Rabbit stomach